Penguatan Critical Thinking Santri Melalui Teknik Muhadharah Di Pondok Pesantren - Junaedi Sitika, Achmad; Sahrurrpmadhon, hikmatiyar; Nurhasanah (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
Muhadharah carried out at the Khairul Bariyyah Islamic Boarding School in Bekasi City can develop and strengthen the critical thinking abilities of students as in the thesis title above, namely "Strengthening Critical Thinking of Santri through Muhadharah Techniques at the Khairul Bariyyah Islamic Boarding School". The aim of this research is to determine the strengthening of students' critical thinking through the muhadharah technique. The subject or focus of this research was aimed at the students of the Khairul Bariyyah Islamic Boarding School as well as the students' supervisors and leaders of the Islamic Boarding School, using a researcher interview instrumentt. Thus, the aim of this research is to describe the implementation of muhadharah activities at the Khairul Bariyyah Islamic Boarding School and how they are implemented in strengthening students' critical thinking by implementing muhadharah activities. The approach used in this research is research with a qualitative approach. Research data was obtained using interviews, observation and documentation methods. The data analysis method is inductive, namely reducing data, presenting data, and drawing conclusions. Based on the research results, it can be concluded that: The approach used in this research is a qualitative approach. Research data was obtained using interviews, observation and documentation methods. The data analysis method was inductive, namely reducing data, presenting data and drawing conclusions.